Analysis of Performance Degradation of the Refrigeration System on MT Nolowati III - Sahrul Romadon; Moejiono; Mochammad Zainuddin; Agus Prawoto; Prima Yudha Yudianto (Journal of Engineering Science and Technology Management (JES-TM), 2026)
The refrigeration unit, also known as the refrigerator, is a crucial auxiliary machine on board the MT Nolowati III, as it is responsible for ensuring the crew remains healthy and refreshed. A common operational issue is the refrigeration unit's inability to reach its designated operating temperature. This includes the meat compartment (-10°C to -12°C) and the vegetable/fruit compartment (+4°C to +10°C). Suboptimal supporting components such as the compressor and thermostat, as well as a lack of standard maintenance, contribute to this issue. Analysis shows that the decline in performance is mostly caused by technical factors, such as dirt covering the condenser or thermostat errors, which disrupt the refrigeration cycle and cause temperature increases. To prevent this, preventative measures focus on regular maintenance, routine condenser cleaning, and performing maintenance work according to the manual's instructions.